(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
The connection of solar activity with physical and biological processes on Earth, which is confirmed by the scientific research of scientists in this field in recent years, attracted the attention of many people to physical processes in the Sun.